An alginate-based encapsulation system for delivery of therapeutic cells to the CNS. Issue 7 (1st February 2022) - Eleftheriadou, Despoina; Evans, Rachael E.; Atkinson, Emily; Abdalla, Ahmed; Gavins, Francesca K. H.; Boyd, Ashleigh S.; Williams, Gareth R.; Knowles, Jonathan C.; Roberton, Victoria H.; Phillips, James B.
Abstract : Novel composite cell encapsulation system: dual-layer, micro-scale beads maintain cell survival while releasing immunomodulatory FK506 in a sustained manner. This biotechnology platform could be applicable for treatment of CNS and other disorders. Abstract : Treatment options for neurodegenerative conditions such as Parkinson's disease have included the delivery of cells which release dopamine or neurotrophic factors to the brain. Here, we report the development of a novel approach for protecting cells after implantation into the central nervous system (CNS), by developing dual-layer alginate beads that encapsulate therapeutic cells and release an immunomodulatory compound in a sustained manner. An optimal alginate formulation was selected with a view to providing a sustained physical barrier between engrafted cells and host tissue, enabling exchange of small molecules while blocking components of the host immune response. In addition, a potent immunosuppressant, FK506, was incorporated into the outer layer of alginate beads using electrosprayed poly-ε-caprolactone core–shell nanoparticles with prolonged release profiles. The stiffness, porosity, stability and ability of the alginate beads to support and protect encapsulated SH-SY5Y cells was demonstrated, and the release profile of FK506 and its effect on T-cell proliferation in vitro was characterized. Collectively, our results indicate this multi-layer encapsulation technology has the potential to be suitable for use in CNS cell delivery, to protect implanted cells from host immune responses whilst providing permeability to nutrients and released therapeutic molecules.